Reproductive context of extremely short sperm in the parasitic wasp Cotesia congregata (Hymenoptera: Braconidae). (26th August 2020) - Bredlau, Justin P; El-Sabrout, Ahmed M; Bressac, Christophe
Abstract: Among adaptive traits under sexual selection, the length of spermatozoa shows high interspecific variation. In insects, extremes exist for both short and long sperm. The spermatozoa of the endoparasitic wasp Cotesia congregata (Say) are the shortest flagellated sperm described in animals, 6.6 µm in length. By comparison, the sperm of Drosophila bifurca are almost 6000 times longer. Thus, C. congregata has the potential to shed light on the selection pressures that drive variation in sperm length in relation to their production and use. The reproductive organs, sperm counts, controlled oviposition and sex ratios were investigated. The testes showed stratified differentiation stages of spermatogenesis, and sperm counts revealed continuous spermatogenesis in the late pupal stage. The small female spermatheca stored ~1000 sperm, resulting in an extremely high sperm concentration. The number of progeny per brood decreased over time until depletion of eggs. Females produced up to 370 daughters, corresponding to the effective use of 34% of the average sperm stock. Haploid males made up a greater proportion of broods in later parasitisms. Sperm miniaturization may be an adaptation to transfer increased quantities for the entire reproductive life of females in the absence of sperm competition but in the reduced space offered by the spermatheca.